ChemInform Abstract: Highly Regioselective Addition of Organozinc Reagents to 2‐Oxo‐1, 2‐dihydropyrimidine‐5‐carboxylates Activated by BF3·OEt2: Synthesis of 2‐Oxo‐1, 2, 3, 4‐tetrahydropyrimidine‐5‐carboxylates. Issue 9 (4th March 2014) - Singh, Kamaljit; Chopra, Rakesh
Abstract The C—4 position of these compounds has an important influence on their calcium channel blocking activity.